The issue of "turning" in Heidegger’s thought in the context of the history of being - Murzicz, Paweł (Hybris, 2020)
The article deals with the issue of turning (Kehre) in the thought of Martin Heidegger. I show that, in Being and time the question of being posed from the perspective of a distinguished being as Dasein has led to the objectification of being, thus rather reproducing instead of overcoming, the so far way of thinking that Heidegger named “metaphysical”. The turning in Heidegger’s thought consists in his effort to make being independent from human being, i.e. he tries to go beyond the transcendental and subjectivist point of view of Dasein by placing historicality of Dasein against the background of the very existence of being. It is not Dasein who designs being, but on the contrary, being designs understanding for Dasein. In this context, I show that the thinking of being postulated by Heidegger takes the form of thinking the very process of historical presencing of the historic types of interpretation of being.